A Heat‐Activated Drug‐Delivery Platform Based on Phosphatidyl‐(oligo)‐glycerol Nanocarrier for Effective Cancer Treatment. Issue 6 (31st March 2021) - Hossann, Martin; Hirschberger, Johannes; Schmidt, Rebecca; Baumgartner, Christine; Zimmermann, Katja; Baer, Silke; Ratzlaff, Christina; Peller, Michael; Troedson, Karin; Limmer, Simone; Brühschwein, Andreas; Dörfelt, Rene; et al.
Abstract : The potential of cancer drugs is not fully exploited due to low tumor uptake and occurrence of systemic side effects, limiting maximum tolerated dose. Actively targeted nanocarriers improve efficacy while minimizing off‐target toxicity. Herein, it is the first time a drug‐delivery platform for heat‐triggered intravascular drug release is described, based on synthetic phosphatidyl‐(oligo)‐glycerols from organic synthesis to preclinical investigation in feline patients. For the nanocarrier formulated doxorubicin (DOX), superior tumor drug delivery and antitumor activity compared with free DOX, conventional liposomal DOX (Caelyx), and temperature‐sensitive lysolipid‐containing DOX‐liposomes in rat sarcoma are demonstrated. In a comparative oncological study with neoadjuvant treatment of feline sarcoma, a metabolic response determined with 18  F‐FDG‐positron emission tomography/magnetic resonance imaging (PET/MRI) and histopathological response after tumor resection are significantly better compared with free DOX, potentially by overcoming drug resistance based on improved intratumoral drug distribution. This novel drug‐delivery platform has great potential for the treatment of locally advanced tumors in humans. Abstract : Neoadjuvant chemotherapy combined with regional hyperthermia has shown to improve survival in patients with locally advanced high‐risk soft tissue sarcoma. Current response rates are less than 30% due to insufficient tumor targeting and drug penetration. DPPG2 ‐TSL‐DOX nanocarrier for heat‐triggered intravascular drug release has the potential to overcome this limitation by significantly improving drug tumor uptake and thereby enhancing response.